Consolidation of temperature-dependent toxicity and thermoregulatory behavior into risk assessments of insecticides under thermal scenarios: A prospective study on Eremias argus. (February 2023) - Wang, Zikang; Nie, Yufan; Yu, Simin; Chen, Li; Zhang, Luyao; Zhu, Wentao; Zhou, Zhiqiang; Diao, Jinling
Graphical abstract: Highlights: With rising temperature, the toxicity of beta-cyfluthrin decreased. With rising temperature, the toxicity of chlorpyrifos increased. Sub-lethal doses of insecticides induced adaptive thermoregulatory behavior. Six different metabolites contributed to changes in thermotaxis. Risk managements of insecticides must consider these effects in ectotherms. Abstract: In this study, the temperature-dependent chemical toxicity of three insecticides and the resulting thermoregulatory (TR) behavior of the lizard Eremias argus have been consolidated into the current risk assessment framework. According to acute dermal toxicity assays, an increase of ambient temperature from 15 °C to 35 °C decreased the acute dermal toxicity of beta-cyfluthrin (BC) but increased the toxicity of chlorpyrifos (CPF). The toxicity of avermectin (AVM) did not show significant temperature-dependent responses. Based on thermal preference trials, lizards changed their body temperature via TR behavior to adaptively reduce toxicity under sub-lethal doses, which can be understood as a "self-rescue" behavior attenuating lethal effects. However, the risk quotient indicated that the effectiveness of this "self-rescue" behavior is limited. Metabolomics analysis showed that six different metabolites (i.e., creatine, glutamate, succinate, N -acetylaspartate, acetylcholine, and lactate) contributed to TR behavior changes. Biochemical assays and insecticide residue results demonstrated that the temperature-dependent toxicity of BC, CPF, and AVM affected lizards in the three aspects of biotransformation, oxidative stress, and neurometabolic interference. This work clarifies the ecotoxicological impacts of representative insecticides on reptiles from toxicological understanding to risk relevance. This knowledge may improve ecological predictions of agrochemical applications in the context of global climate change.